PERUBAHAN BEBERAPA SIFAT FISIS DAN KIMIA PASTA GAMBIR SELAMA PENYIMPANAN - Anwar Kasim; Yoli Sub’han; Netty Sri Indeswari (Jurnal Riset Kimia, 2008)
ABSTRACT Studying about the change of physical and chemical properties Gambir paste during 28 days was conducted in order to know the change primarily the chemical content and physical properties as storage consequences. Experimental design was used completely randomized design for 4, 8, 12, 16, 20, 24, and 28 days storage periods. Replication was two and as a control was used paste non treatment. F-test and T-Dunnet test were applicated for statistical analysis. The result indicated that treatment can not change physical properties but change the chemical properties gambir paste. The initial water contents of gambir paste was 72.26% and after 28 days storage 71.68%. Color of gambir paste was still yellow during storage. The initial non water soluble substance was 6.96% and after 28 days storage 4.69%. The initial non alcohol soluble substance was 14.83% and after 28 days storage 13.15%. The initial chatechin contents was 72.22% and after 28 days storage 65.38%. The initial tannin contents 38.68% and after 28 days storage 35.12%. Total ash content of gambir paste was 2.72%.   Keywords : gambir, paste, storage, change, properties